2016
DOI: 10.1002/ange.201603931
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocenyl Quinone Methide–Thiol Adducts as New Antiproliferative Agents: Synthesis, Metabolic Formation from Ferrociphenols, and Oxidative Transformation

Abstract: Ferrociphenols (FCs)a nd their oxidized, electrophilic quinone methide metabolites (FC-QMs)a re organometallic compounds related to tamoxifent hat exhibit strong antiproliferative properties.T oe valuate the reactivity of FC-QMs toward cellular nucleophiles,w es tudied their reaction with selected thiols.Aseries of new compounds resulting from the addition of these nucleophiles,t he FC-SR adducts,w ere thus synthesized and completely characterized. Such conjugates are formed upon metabolism of FCs by liver mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…We focused initially on the "ferrociphenol" motif (Fc-CC-C 6 H 4 -OH), known to lead to oxidation with formation of a QM in a biological medium. 27,28 Subsequently, we looked at the imide component, which is capable of producing specific ring-opened metabolites.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We focused initially on the "ferrociphenol" motif (Fc-CC-C 6 H 4 -OH), known to lead to oxidation with formation of a QM in a biological medium. 27,28 Subsequently, we looked at the imide component, which is capable of producing specific ring-opened metabolites.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The 1 H NMR spectrum revealed an approximate 3:1 ratio of E/Z isomers, which can be explained by the steric issue we proposed recently. 28 Molecule 3-QM showed a far better stability profile (half-life in acetone of about 10 days!) than the corresponding QM of 1a which was unstable and even started to decompose before oxidation was complete.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vitro studies demonstrated that at least some Ferr metabolites produced in the cell are electrophilic quinonemethides that can induce growth arrest with senescence and apoptosis phenomena . Recently, adducts of these quinonemethides with compounds bearing thiol functional group, as models of some cellular nucleophiles were identified …”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Recently, adducts of these quinonemethides with compounds bearing thiol functional group, as models of some cellular nucleophiles were identified. [12] Metal-based anticancer drugs, such as PhtFerr and Succ-Ferr, are very hydrophobic compounds that cannot be formulated in aqueous solutions easily. [13] Therefore, we both synthetized their respective ester prodrugs Phtester and Succester and also encapsulated them into nanocarriers to overcome the issue of their poor solubility.…”
Section: Introductionmentioning
confidence: 99%